Evaluation of Single-dose Azithromycin Versus Standard Azithromycin/Doxycycline Treatment and Clinical Assessment of Regression Course in Patients with Adult Inclusion Conjunctivitis. (December 2013) - Malamos, Panagiotis; Georgalas, Ilias; Rallis, Konstantinos; Andrianopoulos, Konstantinos; Georgopoulos, Gerasimos; Theodossiadis, Panagiotis; Vergados, Ioannis; Markomichelakis, Nikos N.
Abstract Background: Single-dose azithromycin (AZT) has been proved efficient in treating various human Chlamydia infections. However, it has not been thoroughly tested in patients with adult inclusion conjunctivitis (AIC). It is the aim of this study to perform a comparative evaluation of efficacy and safety of one-day AZT with long-term AZT and doxycycline (DOX) regimens in AIC and to present a clinical profile of regression course of the disease. Materials: Eighty-three consecutive adults, with symptoms and signs of chronic conjunctivitis and positive Polymerase Chain Reaction (PCR) for chlamydia, were randomly assigned in four treatment groups; AZT 1-day 1000 mg orally, AZT 500 mg daily 9 and 14 days and DOX 200 mg 21 days orally. Follow-up visits were scheduled 1 and 2 weeks, 1, 3 and 6 months after treatment completion. PCR was repeated at the 2nd post-treatment week to confirm elimination of infectious agent. Detailed record of subjective symptoms and objective signs was performed at all visits. Retreatment rate among groups was evaluated as primary outcome. Regression rate of symptoms/signs among groups was recorded as secondary outcomes. Results: All treatment groups provided statistically equivalent results of retreatment rate. Statistically significant regression of symptoms/signs was documented, initially from the 1st post-treatment week in general, but 1 month was required for complete patients' relief. Follicles were the most common clinical sign with the earliest regression after successful treatment. Conclusion: Single-dose azithromycin should be considered as equally reliable treatment option, comparing to long-term alternative regimens for AIC. Patients should wait for one week, until first signs of significant regression become obvious and should consider approximately one month to total relief. Follicles could be reasonably used as a key sign for clinical assessment of treatment success.